2016
DOI: 10.1017/s1355617715000995
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Cortical Connectivity in Alzheimer’s Disease as a Brain Neural Network Pathology: Toward Clinical Applications

Abstract: Objectives: The objective was to review the literature on diffusion tensor imaging as well as resting-state functional magnetic resonance imaging and electroencephalography (EEG) to unveil neuroanatomical and neurophysiological substrates of Alzheimer's disease (AD) as a brain neural network pathology affecting structural and functional cortical connectivity underlying human cognition. Methods: We reviewed papers registered in PubMed and other scientific repositories on the use of these techniques in amnesic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 238 publications
(323 reference statements)
3
82
0
1
Order By: Relevance
“…as summarized by Joo 84 . Teipel 85 summarizes studies of cortical connectivity in AD across RS fMRI, EEG rhythms and DTI-defined white matter bundles that explored interrelationships between different forms of brain connectivity. These can be revealing; for example, Patel 86 found no cognitive or white matter FA differences between 14 carriers and 22 non-carriers of ApoE4, but decreased functional connectivity in DMN regions previously implicated in AD on IC.…”
Section: Alzheimer’s Disease and Its Precursor Amnestic Mild Cognitimentioning
confidence: 99%
See 1 more Smart Citation
“…as summarized by Joo 84 . Teipel 85 summarizes studies of cortical connectivity in AD across RS fMRI, EEG rhythms and DTI-defined white matter bundles that explored interrelationships between different forms of brain connectivity. These can be revealing; for example, Patel 86 found no cognitive or white matter FA differences between 14 carriers and 22 non-carriers of ApoE4, but decreased functional connectivity in DMN regions previously implicated in AD on IC.…”
Section: Alzheimer’s Disease and Its Precursor Amnestic Mild Cognitimentioning
confidence: 99%
“…Cortical connectivity in AD has sometimes been described as brain neural network pathology 85 . For example He and others 87,88,79 have adopted network analytic approaches to study AD, and report that the disease is associated with disruption of normal global functional organization affecting not only local connectivity but also specialized hub nodes and important long-distance connections.…”
Section: Alzheimer’s Disease and Its Precursor Amnestic Mild Cognitimentioning
confidence: 99%
“…Similarly, another study detected a negative correlation between memory and mean diffusivity in the frontal, temporal, or primary sensory subregions of the CC in AD and aMCI2. Moreover, based on the network-based neurodegeneration hypothesis14, accumulating evidence has shown that the default mode network (DMN) structure and function is damaged in AD515 and the DMN disruptions were associated with memory deficits161718. For example, Bernard and colleagues have demonstrated that dysconnectivity in precuneus, one core region of the DMN (connected by posterior CC)19, was related to episodic memory deficits in elderly20.…”
mentioning
confidence: 94%
“…Di Paola and colleagues found reduced white matter density in the anterior CC subregion in aMCI compared to controls1. Other studies found splenium of corpus callosum might serve as an early marker to predict progression of aMCI to AD34 (see review5). Mixed findings about diffusivity changes of CC in MCI were also reported126.…”
mentioning
confidence: 99%
“…Cognition and memory are the products of the integrated activity in cortical networks of various hubs/regions (Friston et al 1993;Horwitz 1994;McIntosh 1999;Grady et al 2001;Yonelinas et al 2005); these attributes may decline following disruption in network interactions due to sensory disruptions (Grady et al 2001;Sidhu et al 2013). An ongoing temporal course of sensory dysfunction may lead to dysfunction in the projected nuclei, as well as corticocortical neurocircuitry; this may thus underpin white and gray matter atrophy in the pathogenesis of AD (Greicius et al 2004;Jones et al 2016;Teipel et al 2016).…”
Section: Neurotox Resmentioning
confidence: 99%